Pengaruh Distribusi Terhadap Kepuasan Pelanggan Pada PT. JNE (Jalur Nugraha Ekakurir) Express Kota Gunungsitoli - Ester Seniwati Zebua; Nov Elhan Gea; Maria M. Bate'e; Otanius Laia (Visi Sosial Humaniora, 2024)
This research is based on the distribution channels of goods and services carried out by a service company and their influence on customer satisfaction. Distribution activities are important for the continuity of a company's business, so these activities must be carried out in order to satisfy and of course retain customers. For this reason, suppliers must be able to distribute orders on time. This research was carried out at PT. JNE Express Gunungsitoli City with the aim of finding out whether there is an influence of distribution on customer satisfaction and how much influence distribution has on customer satisfaction. This research uses quantitative methods with a sample size of 36, namely employees and customers of PT. JNE Express. Data analysis uses the t test to determine the influence of the independent variable on the attachment variable and the determinant coefficient to determine how much influence is given with the help of SPSS 24. Based on hypothesis testing, it can be concluded that distribution influences customer satisfaction at PT. JNE Express Gunungsitoli City with a significance value of 0.000 < 0.05. The research results show that distribution contributes 66% to customer satisfaction and the rest is determined by other circumstances. The results of the research recommend improvements in increasing distribution services provided to consumers, especially in the distribution of goods and the need for strict supervision of couriers who deliver goods from companies to consumers. There are still many couriers who delay the delivery of goods and do not convey clear information to consumers so there are many consumer complaints regarding the services provided